EXPLORING LAND CONFLICTS IN NGUGI WA THIONGO’S PETALS OF BLOOD (1977) AND DEVIL ON THE CROSS (1980) - HOUNDJO_, FLORE ARMANDE (My University, 2023)
This paper aims at giving more insights into how land conflicts are dealt with by Ngugi Wa Thiong’o in such selected novels as Petals of Blood and Devil on the Cross. In these novels, the Kenyan writer raises the thoughtprovoking issue of the great responsibility befalling Africans at large and African decision-makers in particular as regards how they can reverse the trend today by really managing their own domestic affairs after the achievement of the hard-won independence of their countries. Through the lens of post-colonial criticism, psychoanalysis and Marxist literary criticism coupled with qualitative data approach, this paper arouses Africans’ awareness on the role that they have to play with a view to paving the way for their continent’s development. The results of our findings lead us to impart to the reader how the responsibility befalling Africans to really achieve their own empowerment in this globalised world is quite tremendous. With this in view, Africans at large and African decision-makers in particular need to show the former colonial powers that after the independences, they are really committed to putting their respective countries on the path of development through a healthier and profitable cooperation with advanced countries.
Keywords: Land; Conflicts; Ngugi; Petals of Blood; Devil on the Cross.